2006
DOI: 10.1111/j.1746-6342.2006.00034.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of plasma ghrelin in peptic ulcer disease

Abstract: Summary Background Ghrelin is a novel appetite‐promoting peptide secreted primarily from the A‐like cells in the gastric fundic mucosa. As gastric inflammation caused by Helicobacter pylori infection extends, the number of ghrelin‐producing A‐like cells is diminished and gastric ghrelin content decreases significantly. We previously reported that plasma levels of ghrelin, which correlated well with the serum levels of pepsinogen (PG) I and PG I/II ratio, decreased as gastric mucosal atrophy increased in non‐ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…76,77 On the other hand, plasma ghrelin levels are increased when peptic ulceration is present. 78,79 With regard to the role of ghrelin in FD, Shinomiya et al 80 reported a significant correlation between circulat- ing levels of acylated ghrelin and the subjective symptom score in FD patients. We also reported that, in patients with FD, and especially in those with dysmotility-like FD, plasma levels of ghrelin are significantly increased, 45 suggesting that compensatory secretion of ghrelin may be enhanced in patients with FD in order to normalize the impaired GI motility (dysmotility).…”
Section: Expected Therapeutic Targets In the Field Of Fdmentioning
confidence: 98%
“…76,77 On the other hand, plasma ghrelin levels are increased when peptic ulceration is present. 78,79 With regard to the role of ghrelin in FD, Shinomiya et al 80 reported a significant correlation between circulat- ing levels of acylated ghrelin and the subjective symptom score in FD patients. We also reported that, in patients with FD, and especially in those with dysmotility-like FD, plasma levels of ghrelin are significantly increased, 45 suggesting that compensatory secretion of ghrelin may be enhanced in patients with FD in order to normalize the impaired GI motility (dysmotility).…”
Section: Expected Therapeutic Targets In the Field Of Fdmentioning
confidence: 98%